Difference between the Actual and Labeled Concentrations of Several Domestic Brands of Sodium Hypochlorite - Saberi, Eshagh Ali; Farhad-Mollashahi, Narges; Saberi, Mersad (Iranian Endodontic Journal, 2019)
Introduction: Sodium hypochlorite (NaOCl) is extensively used in root canal treatment and its efficacy depends on the concentration of free available chlorine (FAC). This study aimed to assess the chlorine content of 10 domestically manufactured household bleach products available in the Iranian market and evaluate the effect of temperature, time and daily bottle uncapping on FAC concentration and pH of these products. Methods and Materials: One-liter bottles of 10 available brands of household bleach (n=4 of each brand) were collected and randomly divided into four groups (n=10). Two groups were refrigerated at 4°C while the remaining two were stored at room temperature. One group of refrigerated and one group of room temperature samples were subjected to daily bottle uncapping followed by agitation and recapping for 3 months (six times a week to simulate weekly office work). The remaining bottles remained untouched and served as controls. The concentration of FAC in each sample was measured using the iodometric titration assay, and the pH was measured using a calibrated pH-meter at baseline and 1, 2 and 3 months. The results were analyzed using the one-way ANOVA and t-test. Results: The mean concentration of FAC in the solutions was 4.87±0.19% at baseline. The measured concentration of sodium hypochlorite was different from the labeled value. The concentration of FAC decreased over time in all samples; the greatest reduction occurred in room temperature samples subjected to daily uncapping while the smallest reduction occurred in refrigerated, capped bottles (19% and 1.9%, respectively). The pH of all products decreased over time. The mean reduction in pH was 1.1 for the samples stored at room temperature for 3 months and 0.8 for the refrigerated samples. Conclusion: This in vitro study showed that the expected concentration of sodium hypochlorite solution made of household bleach for endodontic purposes is different from its actual concentration. Keywords: Chlorine Compounds; Hydrogen-ion Concentration; Root Canal; Sodium Hypochlorite